High‐resolution modeling of atmospheric dynamics in the Nepalese Himalaya. Issue 19 (5th October 2015) - Collier, Emily; Immerzeel, Walter W.
Abstract High‐altitude meteorological processes in the Himalaya are influenced by complex interactions between the topography and the monsoon and westerly circulation systems. In this study, we use the Weather Research and Forecasting model configured with high spatial resolution to understand seasonal patterns of near‐surface meteorological fields and precipitation processes in the Langtang catchment in the central Himalaya. Using a unique high‐altitude observational network, we evaluate a simulation from 17 June 2012 to 16 June 2013 and conclude that, at 1 km horizontal grid spacing, the model captures the main features of observed meteorological variability in the catchment. The finer representation of the complex terrain and explicit simulation of convection at this grid spacing give strong improvements in near‐surface air temperature and small improvements in precipitation, in particular in the magnitudes of daytime convective precipitation and at higher elevations. The seasonal differences are noteworthy, including a reversal in the vertical and along‐valley distributions of precipitation between the monsoon and winter seasons, with peak values simulated at lower altitudes (~3000 m above sea level (asl)) and in the upper regions (above 5000 m asl) in each season, respectively. We conclude that there is great potential for improving the local accuracy of climate change impact studies in the Himalaya by using high‐resolution atmospheric models to generate the forcing for such studies.